Highlighting the Urgent Need for Reforms in the Face of Financial Failures at State-Owned Enterprises in Iraq: Menyoroti Kebutuhan Mendesak untuk Reformasi dalam Menghadapi Kegagalan Keuangan pada Perusahaan Milik Negara di Irak - Hasan, Ibrahim Naeem (Academia Open, 2024)
General Background: The financial analysis of companies' reports is critical for assessing their past performance, forecasting future results, and identifying operational strengths and weaknesses. Specific Background: Financial failure, which occurs when a company cannot generate adequate returns to cover costs and capital expenses, poses significant risks to stakeholders. For state-owned companies, the implications of financial failure are especially profound, given their integral role in national economies, such as Iraq's. Knowledge Gap: There is limited understanding of the extent to which state-owned companies in Iraq utilize financial analysis to predict financial failure, particularly in the context of economic transitions and privatization pressures. Aims: This study aims to evaluate the dependence of Iraqi state-owned companies on financial analysis as a predictive tool for financial distress and to identify the key factors contributing to their financial failures. Results: The research reveals that 42% of the companies examined have experienced financial failure, as measured by the Argenti index. Contributing factors include employment challenges, insufficient financing, and the transition from a socialist to a capitalist economy, which has left companies vulnerable to privatization. Novelty: The study provides novel insights into how economic transition impacts the financial stability of state-owned companies, highlighting the practical application of the Argenti index in diagnosing financial weaknesses. Implications: The findings underscore the urgent need to support state-owned enterprises by revitalizing the industrial sector, improving administrative efficiency, and adopting more systematic financial analysis tools. Additionally, the research recommends creating an accessible information center for investors and creditors, which would enhance transparency and support decision-making. This approach could help mitigate financial distress and attract new investment, ultimately contributing to Iraq’s economic recovery. Highlights: Financial analysis helps predict failures in state-owned companies. 42% of companies fail, based on the Argenti index. Privatization and economic shifts increase financial risk. Keywords: Financial analysis, Argenti index, state-owned companies, financial failure, privatization